Morbidity and Mortality of COVID in Relation to Age, Sex and BMI - Bhagavan, Mysore S.; Karnatapu, Srikrishna C.; Doke, Saloni; Amalathasan, Theourrn; Amalathasan, Thebuoshon; Ashokkumar, Chiraag (ABC Journal of Advanced Research, 2022)
The United States (US) has been the epicenter of the Coronavirus disease pandemic (COVID-19). The underrepresented minorities which tend to have a higher prevalence of obesity are affected disproportionately. The objective of this study was to assess the early outcomes and characteristics of COVID-19 patients in the US and also investigate whether age, gender, and obesity are associated with worse outcomes. To determine the effect of body mass index, sex, and age on risk for morbidity and mortality of COVID-19. Compressive systematic research was conducted to pool every relevant article that evaluated COVID’s effect on patients with regard to BMI, age, sex, and mortality. Search for articles was conducted in the most widely-used databases such as PubMed, Scopus, EMBASE, and Web of Science. Search terms used for article retrieval included: “BMI,” OR “Obesity,” OR “BMI,” OR “Sex,” OR “Age.” AND “COVID-19 related mortality.” Severe obesity, male sex, and increasing age are associated with a high rate of in-hospital mortality and generally, worse in-hospital prognosis.